2014
DOI: 10.1088/0004-637x/782/2/68
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter Galaxies as Progenitors of Compact Quiescent Galaxies

Abstract: Three billion years after the big bang (at redshift z = 2), half of the most massive galaxies were already old, quiescent systems with little to no residual star formation and extremely compact with stellar mass densities at least an order of magnitude larger than in low redshift ellipticals, their descendants. Little is known about how they formed, but their evolved, dense stellar populations suggest formation within intense, compact starbursts 1-2 Gyr earlier (at 3 < z < 6). Simulations show that gas-rich ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
365
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 293 publications
(399 citation statements)
references
References 135 publications
31
365
1
2
Order By: Relevance
“…N is the number of sources in each sample. The last column is the weighted mean with the associated error obtained following the procedure described in Section 3.1. are consistent with the typical values of dust-rich systems such as sub-millimetre galaxies (SMGs), whose dust content is of the order of M dust = 9 × 10 9 M (e.g, Kovacs et al 2006;Toft et al 2014). …”
Section: Ism Mass Estimatessupporting
confidence: 85%
“…N is the number of sources in each sample. The last column is the weighted mean with the associated error obtained following the procedure described in Section 3.1. are consistent with the typical values of dust-rich systems such as sub-millimetre galaxies (SMGs), whose dust content is of the order of M dust = 9 × 10 9 M (e.g, Kovacs et al 2006;Toft et al 2014). …”
Section: Ism Mass Estimatessupporting
confidence: 85%
“…Di Matteo, Springel & Hernquist 2005), possibly resulting in compact quiescent galaxies (e.g. Toft et al 2014). It has been speculated that SMGs could then evolve on to the scaling relations observed for massive local elliptical galaxies, based on simple arguments involving the time-scale of the burst and the ageing of the stellar population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…From an observational point of view, this is supported by the clumpy or disturbed morphologies of SMGs and their complex kinematic signatures (e.g. Smail et al 1998;Tacconi et al 2008;Engel et al 2010;;Sharon et al 2013;Riechers et al 2013Riechers et al , 2014Hung et al 2013;Toft et al 2014;Neri et al 2014;Chen et al 2015). Engel et al (2010) concluded that most of the SMGs with IR luminosities of L IR > ∼ 5 × 10 12 L are probably major-merger systems (i.e.…”
mentioning
confidence: 97%
“…with little or no ongoing star formation) elliptical galaxies seen in the present-day universe (e.g. Lilly et al 1999;Swinbank et al 2006;Fu et al 2013;Toft et al 2014;Simpson et al 2014). The existence of quiescent, red massive galaxies already at z ∼ 2−3 with old stellar populations indicates that these galaxies have experienced a short-lived starburst phase in their past (e.g.…”
mentioning
confidence: 99%